2020
DOI: 10.1016/j.bonr.2020.100725
|View full text |Cite
|
Sign up to set email alerts
|

The mortality burden of non-trauma fracture for adults with cerebral palsy

Abstract: Background Individuals with cerebral palsy (CP) manifest skeletal fragility problems early in life, are vulnerable to non-trauma fracture (NTFx), and have a high burden of premature mortality. No studies have examined the contribution of NTFx to mortality among adults with CP. The purpose of this study was to determine if NTFx is a risk factor for mortality among adults with CP and if NTFx exacerbates mortality risk compared to adults without CP. Methods Data from 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…This may shed some light on a newly forming concept in the field that bone fragility is implicated in the pathogenesis of unhealthful aging for adults with cerebral palsy. A recent epidemiologic study have found that sustaining a fragility fracture is a robust risk factor for premature mortality for adults with cerebral palsy, even after accounting for demographics, cardiorespiratory diseases, diabetes, cancer, and kidney disease ( 40 ). Additional epidemiologic studies have also found that fragility fractures are a robust risk factor for incidence of several cardiorespiratory diseases for adults with cerebral palsy ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may shed some light on a newly forming concept in the field that bone fragility is implicated in the pathogenesis of unhealthful aging for adults with cerebral palsy. A recent epidemiologic study have found that sustaining a fragility fracture is a robust risk factor for premature mortality for adults with cerebral palsy, even after accounting for demographics, cardiorespiratory diseases, diabetes, cancer, and kidney disease ( 40 ). Additional epidemiologic studies have also found that fragility fractures are a robust risk factor for incidence of several cardiorespiratory diseases for adults with cerebral palsy ( 41 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adults ≥18 years of age with CP were identified by searching for at least one claim for CP which covered all diagnostic CP types (eg, quadriplegia), as previously described, including codes. 16–19 Data about the severity of CP using common clinical measures (eg, gross motor function classification system) are not available in insurance claims. Further, >70% of the CP sample had “other” or “unspecified” CP.…”
Section: Methodsmentioning
confidence: 99%
“…Guided by the literature, 32–34 fracture of the vertebral column, hip (including proximal femur), non-proximal femur, tibia/fibula, humerus, ulna/radius, or unspecified location without trauma codes (eg, vehicle accident) 7 days before to 7 days after the index fracture date was defined as NTFx, as previously described, 16–19 and all other fractures were considered trauma fractures. Fractures in the pre-index time period was identified as trauma or non-trauma and by each site.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations